2020
DOI: 10.3390/app11010159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbonyl and Hydroxyl Compounds Addition on CO2 Injection through Hydrocarbon Extraction Processes

Abstract: CO2 miscible flooding occurs when injection pressure is higher than the minimum miscibility pressure (MMP) which can exceed the fracture pressure. Co-solvents are expected to reduce the MMP by interacting with various hydrocarbons that depend on the polarity and intermolecular forces of solvent and oil. However, there are limited studies that have investigated co-solvent performance in CO2 injection through an extraction process based on oil compositional analysis. This paper is aimed at studying the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The samples were pollinated after drying in an oven, while extraction was carried out with the combined sonication-maceration method. The solvent used was 70% ethanol which can extract both polar and non-polar organic compounds from the sample (Permadi et al 2021). After obtaining the extract, phytochemical screening was conducted to determine the class of active compounds from the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were pollinated after drying in an oven, while extraction was carried out with the combined sonication-maceration method. The solvent used was 70% ethanol which can extract both polar and non-polar organic compounds from the sample (Permadi et al 2021). After obtaining the extract, phytochemical screening was conducted to determine the class of active compounds from the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Permadi et al 91 found that low-carbon alcohols, such as methanol and ethanol, can enhance the extraction performance of CO 2 , thereby reducing MMP.…”
Section: Mmp Reducing Techniquesmentioning
confidence: 99%
“…There were studies that indicate the limitations of the disk diffusion method when it comes to the lack of diffusion of non-polar molecules into the aqueous agar matrix that is used in the assay (Eloff, 2019). Although ethanol is generally a polar solvent, it has a non-polar structure which helps in its ability to also extract non-polar compounds (Permadi et al, 2020). It is possible that the ethanol extract of P. betle may also contain nonpolar molecules which had antimicrobial activity but was not able to diffuse well into the agar.…”
Section: Antimicrobial Activity and Minimum Inhibitory Concentration ...mentioning
confidence: 99%